Early experiences using bromelain-based enzymatic debridement in a tertiary burns centre in the United Kingdom: A retrospective case series review. Issue 6 (June 2021) - Arkoulis, Nikolaos; Mabvuure, Nigel Tapiwa; Smith, Alex; Barnes, David E.
Summary: Background: The modern ethos of burn care requires a holistic approach that helps patients to not only survive but also maintain a good quality of life. Bromelain-based enzymatic debridement with Nexobrid™ (NXB) has been shown to selectively debride burnt tissue and allow dermal preservation, which has the potential to reduce surgical burden and improve scarring. In this study, early experience with the use of Nexobrid™ at a tertiary burns centre between July 2016 and December 2019 is presented. In particular, the study assessed whether NXB had changed the acute care delivered to this cohort. Methods: A retrospective analysis of the patients' records was performed. Results were analysed and presented in the context of current literature. Results: Twenty adult patients (17 male, 3 female) underwent enzymatic debridement with NXB. Median age was 42.5 years. Mean total burn surface area (TBSA) on admission was 20%. Twelve patients were admitted to the intensive care unit, and eight were admitted to the adult burns ward. Mean TBSA treated with NXB was 8.2%, usually within 24 h of admission (mean). All patients had anaesthetist-led analgesia. NXB debridement was successful in 55% of patients, obviating the need for escharotomy in some patients. Sixty percent of all patients required further surgery, and 80% of facial burns treated with NXB required further surgery. Inotrope support was associated with NXB failure ( p  = 0.015). Mean length of stay was 29 days. Discussion: Current evidence, including our own findings, cannot justify replacing the current surgical standard of care with NXB, but it certainly solidifies enzymatic debridement as a useful adjunct that should form part of the modern burn surgeon's armamentarium.